Spin-valley dynamics of electrically driven ambipolar carbon-nanotube quantum dots. (8th June 2017) - Osika, E N; Chacón, A; Lewenstein, M; Szafran, B
Abstract: An ambipolar n – p double quantum dot defined by potential variation along a semiconducting carbon-nanotube is considered. We focus on the (1e, 1h) charge configuration with a single excess electron of the conduction band confined in the n -type dot and a single missing electron in the valence band state of the p -type dot for which lifting of the Pauli blockade of the current was observed in the electric-dipole spin resonance (Laird et al 2013 Nat. Nanotechnol .8 565). The dynamics of the system driven by periodic electric field is studied with the Floquet theory and the time-dependent configuration interaction method with the single-electron spin-valley-orbitals determined for atomistic tight-binding Hamiltonian. We find that the transitions lifting the Pauli blockade are strongly influenced by coupling to a vacuum state with an empty n dot and a fully filled p dot. The coupling shifts the transition energies and strongly modifies the effective g factors for axial magnetic field. The coupling is modulated by the bias between the dots but it appears effective for surprisingly large energy splitting between the (1e, 1h) ground state and the vacuum (0e, 0h) state. Multiphoton transitions and high harmonic generation effects are also discussed.